Pasiëntonderrigstandaarde vir verpleegpraktyk in algemene hospitale - L.R. Uys; M.J. Viljoen; M.V. Vermaak; M. Muller; L Coetzee (AOSIS, 1990)
A lack o f patient education standards was identified and the researchers attempted in this study to develop standards for patient education. An instrument fo r the evaluation o f patient knowledge was also developed.